2021
DOI: 10.5853/jos.2020.05225
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Recurrence in First-Ever Symptomatic Carotid Web: A Cohort Study

Abstract: Background and Purpose Carotid web (CaW) is an intimal variant of fibromuscular dysplasia responsible for ipsilateral cerebral ischemic events (CIE). Symptomatic CaW likely has a high risk of recurrent CIE, but no salient prospective data are available. We aimed to assess recurrence rate and its predictors after a first-ever CIE.Methods Consecutive Afro-Caribbean patients who had cryptogenic first-ever CIEs (ischemic stroke [IS] or transient ischemic attack [TIA]) associated with ipsilateral CaW were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
4
23
1
Order By: Relevance
“…In addition, fourteen patients (82.4%) experienced AIS. There was no significant difference when looking at the prevalence of the left CaW group and the right CaW group, which is consistent with previous study ( 25 ). Moreover, our results showed that there were statistical differences in the thrombosis between the <60 years old CaW group and the ≥60 years old CaW group ( P = 0.005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, fourteen patients (82.4%) experienced AIS. There was no significant difference when looking at the prevalence of the left CaW group and the right CaW group, which is consistent with previous study ( 25 ). Moreover, our results showed that there were statistical differences in the thrombosis between the <60 years old CaW group and the ≥60 years old CaW group ( P = 0.005).…”
Section: Discussionsupporting
confidence: 92%
“…However, whether any of these treatment strategies are optimal remains unclear. Medical management alone has a higher recurrence rate ( 25 ). Although surgery is a first-line treatment strategy, patients may be at risk of vascular occlusion and more severe carotid stenosis ( 25 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Several studies suggest that patients with symptomatic CW have a high risk of recurrent stroke, even if they receive medical treatment. [4][5][6] Carotid revascularization may be safe and effective in patients with CW. 6,7 However, many clinicians have insufficient understanding of CW.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Carotid revascularization may be safe and effective in patients with CW. 6,7 However, many clinicians have insufficient understanding of CW. It is easy for it to escape diagnosis or be misdiagnosed, since it rarely causes hemodynamic stenosis.…”
Section: Introductionmentioning
confidence: 99%